Values through Translation: A Study on the Translated Short Stories by Kekirawa Suleiha. - Gayathree, S. (Vavuniya Campus of the University of Jaffna, 2017)
Translation unites various cultures, values, norms and traditions. The success of a translation depends upon making the readers to be curious enough to read the original by giving a complete picture of the original with the preservation of the style and manner and the ease of the original. Short stories teach and depict some moral values. These should be aptly carried out into the translation. This study aims at identifying the exact transference of these values into the translated short stories by KekirawaSuleiha. The short stories 'Thakur's Well' by Premchand and 'Stench of Kerosene' by Amrita Pritam have been translated by Kekirawa Suleiha respectively as (Thakurin Kinaru) and LDG Q4 (Mannei Nedi) which appeared in the collection titled o Gong (Vaanambadiyum Roojaavum) are taken for analysis in this study. A critical analysis is made to identify the exact transference of the values and the strategies utilized in this translation. Identifying the exact transference and inferring the strategies may be helpful to the translators in future.
Keywords: Short Stories; Moral Values; Exact Transference; Strategies